2010
DOI: 10.3171/2010.6.spine10167
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival in patients with prostate cancer and spinal metastasis

Abstract: The results of this study are important for oncologists, neurosurgeons, and primary care physicians who have patients with prostate cancer that metastasizes to the spine, because these results can be used to form a prognosis and guide the physician in making appropriate decisions regarding the patient's treatment. Future work should include building a predictive model that accurately determines survival in patients with metastatic disease, because this would guide the physician in devising the most appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…However, the median survival of lung cancer with bone metastases is 6-7 months [8]. Recently, a retrospective observational study showed that the median overall survival after diagnosis of prostate cancer with spinal metastases was 24 months with an estimated 1-year overall survival of 73 % [9]. The median survival time after diagnosis of breast cancer with bone metastases was 32 months [10].…”
Section: Prognosismentioning
confidence: 98%
“…However, the median survival of lung cancer with bone metastases is 6-7 months [8]. Recently, a retrospective observational study showed that the median overall survival after diagnosis of prostate cancer with spinal metastases was 24 months with an estimated 1-year overall survival of 73 % [9]. The median survival time after diagnosis of breast cancer with bone metastases was 32 months [10].…”
Section: Prognosismentioning
confidence: 98%
“…This study corroborates previous research findings regarding prognosis after bone metastasis. [10][11][12] As noted by Ibrahim et al, most bone metastasis are secondary to breast, prostate and lung cancer. 5 Generally, the 1-year survival rates observed in the present study are lower than other clinical based studies.…”
mentioning
confidence: 94%
“…7 8 Population-based reports on length of survival after bone metastases from many primary cancer types are lacking. In patients with breast, prostate and renal cancer, the reported median survival ranges from 12 to 33 months for patients with bone metastases, [9][10][11][12][13][14] and survival increases with longer time between primary diagnosis and such metastases. 15 On the other hand, survival is low for patients with primary lung cancer and bone metastases, 1-year survival ranging from 9.5% to 12%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite significant improvements in local and systemic therapies, most deaths from prostate cancer are due to metastasis which resist conventional therapies (2)(3)(4). Therefore, novel therapeutic strategies targeting specific molecular markers are being pursued to allow early detection and cure.…”
Section: Introductionmentioning
confidence: 99%